Review of the Financial Sector Assessment Program-Further Adaptation to the Post-Crisis Era. (Policy Papers; Policy Paper ;, 2014)
The Financial Sector Assessment Program (FSAP), established in 1999, is an in-depth assessment of a country's financial sector. It is an important element of the Fund's surveillance and provides input to the Article IV consultations. In developing and emerging market countries, FSAP assessments are usually conducted jointly with the World Bank and include two components: a financial stability assessment (the main responsibility of the Fund) and a financial development assessment (the main responsibility of the World Bank). Each FSAP concludes with the preparation of a Financial System Stability Assessment (FSSA), which focuses on issues of relevance to IMF surveillance and is discussed by the IMF Executive Board normally together with the country's Article IV staff report. Since the program's inception, 144 member countries have requested and undergone FSAPs, most of them more than once. In recent years, the Fund has been conducting 14-16 FSAPs per year at an annual cost of USD 13-15 million. The last review of the FSAP in 2009, in the aftermath of the global financial crisis, introduced a number of far-reaching reforms that have clarified the responsibilities of the Fund and the Bank in developing and emerging market countries, where assessments usually take place jointly, established institutional accountability, strengthened the analytical focus and coverage of FSAPs, and introduced the option of modular assessments that has afforded the Fund and national authorities greater flexibility on the scope and timing of assessments. In 2010, the financial stability assessment under the FSAP in 25 jurisdictions with financial sectors deemed by the Fund to be systemically important became a mandatory part of Article IV surveillance, expected to take place every five years. The list was expanded to 29 jurisdictions in 2013. For all other jurisdictions, FSAP participation continues to be voluntary.In 2010, the financial stability assessment under the FSAP in 25 jurisdictions with financial sectors deemed by the Fund to be systemically important became a mandatory part of Article IV surveillance, expected to take place every five years. The list was expanded to 29 jurisdictions in 2013. For all other jurisdictions, FSAP participation continues to be voluntary.